List of IMF Member Countries with Delays in Completion of Article IV Consultations or Mandatory Financial Stability Assessments over 18 Months. - International Monetary Fund. Legal Dept. (Washington, D.C. : International Monetary Fund, 2019)
In line with the framework for addressing excessive delays in the completion of Article IV consultations, the following table lists the IMF members for whom the Article IV consultation has been delayed by more than 18 months as of December 15, 2018.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: External Website; List Of Member Country; PP; Website